Model Problem-Based Learning for Improving Student’s Mathematical Competence: Systematic Literature Review - M. Azhari Panjaitan; Suhendra Suhendra (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
Improving students' mathematical competence such as problem-solving skills, mathematical communication, reasoning, and others can use the Problem Based Learning model. This study aims to analyze the impact of the Problem Based Learning model in improving the mathematical competence of students from primary school, junior high, and senior high school levels. The research method used is Systematic Literature Review (SLR). The sample comprises 17 research results on the PBL model in improving students' mathematical competence (concept understanding, problem-solving, and communication skills). The sample comes from indexed journals from the period 2012-2019. The key research question is how PBL influences students' mathematical competence based on the year of school, level of study, research location, and sample size. The SLR method can find an increase in the number of eight-year studies. The results showed that communication skills and understanding of mathematical concepts dominated research results in improving mathematical abilities through problem-based learning models. Most of the research was conducted at the junior high school level outside Java, with a sample size of 30 people or more. Based on the results of the review, the study’s conclusion proves the influence of the Problem Based Learning (PBL) model on students' mathematical competence.